AGRONOMIC CHARACTERISTICS OF CAULIFLOWER (Brassica oleracea var. Botrytis L.) DUE TO APPLICATION OF VARIOUS DOSAGES OF BOKASHI FERTILIZER AND LEAF DEFOLIATION - Yatmin Yatmin; Affan Prasetya; Nurleni Kurniawati; Maryati Maryati (International Journal of Artificial Intelligence Research, 2022)
Cauliflower plants are one of the horticultural crops that are generally cultivated in sub-tropical lands. Along with the times, this plant began to be cultivated in the lowlands, another problem with cauliflower cultivation in the lowlands is that it has a longer vegetative phase, so it has more leaves than in the highlands which results in the length of time the plant enters the generative phase. Cauliflower cultivation in Indonesia still applies conventional farming using chemical fertilizers. The impact of using chemical fertilizers will leave residues on the soil and the environment, so it is necessary to use environmentally friendly fertilizers such as cow bokashi fertilizer. This research was conducted in Untoro Village, Trimurjo District, Central Lampung Regency, from August to October 2022. The experiment was arranged based on a factorial Complete Randomized Block Design (RAKL) with two factors repeated 3 times. The first factor was the dose of bokashi which consisted of three levels, namely 150, 300 and 450 g/polybag. The second factor was leaf defoliation which consisted of 3 levels, namely 0, 4, and 8 leaves/plant. From the results of this study it can be concluded that the independent effect of the dose of bokashi fertilizer has an effect on the weight of the heads without leaves, leaf defoliation has a significant effect on the flowering time variable. There was an interaction between the application of bokashi fertilizer and leaf defoliation in the root-shoot ratio variable. Provision of bokashi fertilizer for cauliflower plants in the lowlands should use a minimum dose of 450 g/polybag equivalent to 90 tons/ha or higher and further research is needed to determine the appropriate level of defoliation in these varieties.